1997
DOI: 10.1146/annurev.publhealth.18.1.463
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Poverty on Child Health and Development

Abstract: Poverty has been shown to negatively influence child health and development along a number of dimensions. For example, poverty-net of a variety of potentially confounding factors-is associated with increased neonatal and postneonatal mortality rates, greater risk of injuries resulting from accidents or physical abuse/neglect, higher risk for asthma, and lower developmental scores in a range of tests at multiple ages.Despite the extensive literature available that addresses the relationship between poverty and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
293
0
22

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 449 publications
(329 citation statements)
references
References 77 publications
14
293
0
22
Order By: Relevance
“…Consistently across studies, results indicate that growing up in impoverished environments is detrimental (19,20). This includes premature mortality (20), worse cardiovascular health (21), declines in mental health (22), increased mobility impairments (23), and poor immune system function (24). The pathways linking poverty to adult health have been described and involve biological (e.g., physiological impact of poverty) and behavioral (e.g., engaging in negative health behaviors such as smoking) factors (19,20,(24)(25)(26)(27)(28).…”
Section: Poverty Nonparental Care and Healthsupporting
confidence: 59%
See 2 more Smart Citations
“…Consistently across studies, results indicate that growing up in impoverished environments is detrimental (19,20). This includes premature mortality (20), worse cardiovascular health (21), declines in mental health (22), increased mobility impairments (23), and poor immune system function (24). The pathways linking poverty to adult health have been described and involve biological (e.g., physiological impact of poverty) and behavioral (e.g., engaging in negative health behaviors such as smoking) factors (19,20,(24)(25)(26)(27)(28).…”
Section: Poverty Nonparental Care and Healthsupporting
confidence: 59%
“…The implications of poverty reach beyond financial resources to include access to services and benefits, social capital, and educational opportunities (19). Consistently across studies, results indicate that growing up in impoverished environments is detrimental (19,20). This includes premature mortality (20), worse cardiovascular health (21), declines in mental health (22), increased mobility impairments (23), and poor immune system function (24).…”
Section: Poverty Nonparental Care and Healthmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous published studies have shown worse health outcomes for the povertystricken. [32][33][34] Mojtabai and Olfson in an analysis of adherence and income in patients observed a 13% increase in non adherence for the low income. They measured adjusted odds ratios of 1.49 and 1.75 for the outcome of 'hospitalization in the past 2 years' and the outcome of 'health got worse' respectively for patients with poor adherence due to costs.…”
Section: Discussionmentioning
confidence: 98%
“…Among the more obvious factors is the household's socioeconomic status which influences its ability to provide better health care for its children and other amenities which affect health (e.g. food with adequate nutrients, proper clothing, clean tap water, clean sanitary conditions) (Aber et al 1997, Defo 1997, Barrett and Browne 1996.…”
Section: What Explains These Patterns? 10mentioning
confidence: 99%